Incentives and Training’s Impact on Real Estate Developer’s Employee Performance: Mediated by Motivation - Pradana, Arkan Ananta; Pradhipta, Yudhistira; Suyoto, Suyoto; Innayah, Maulida Nurul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research investigates how work motivation mediates the impact of incentives and job training on employee performance at PT Pumas Basata Purwokerto, a real estate firm. Utilizing Maslow's hierarchy of needs theory, the research applied a purposive sampling method with 122 respondents and analyzed data using the Partial Least Squares (PLS) approach and Structural Equation Modeling (SEM). This research uses several tests in SPLS, including the outer model test, inner model test, bootstrapping, and blindfolding test. The findings reveal that incentives, job training, and work motivation positively and significantly influence employee performance. Notably, work motivation could mediate the role of job training and incentives toward employee performance, suggesting that enhancing work motivation is essential for improving employee performance. Additionally, increased incentives and job training directly lead to better employee performance.